High contrast reflectance imaging of simulated lesions on tooth occlusal surfaces at near‐IR wavelengths. Issue 8 (16th July 2013) - Fried, William A.; Fried, Daniel; Chan, Kenneth H.; Darling, Cynthia L.
Abstract Introduction In vivo and in vitro studies have shown that high contrast images of tooth demineralization can be acquired in the near‐infrared (near‐IR) without the interference of stain. The purpose of this study is to compare the lesion contrast in reflectance at near‐IR wavelengths coincident with high water absorption with those in the visible, the near‐IR at 1, 300 nm and with fluorescence measurements for early lesions in occlusal surfaces. Methods Twenty‐four human molars were used in this in vitro study. Teeth were painted with an acid‐resistant varnish, leaving a 4 × 4 mm window in the occlusal surface of each tooth exposed for demineralization. Artificial lesions were produced in the exposed windows after 1‐ and 2‐day exposure to a demineralizing solution at pH 4.5. Lesions were imaged using near‐IR reflectance at three wavelengths, 1, 300, 1, 460, and 1, 600 nm using a high definition InGaAs camera. Visible light reflectance, and fluorescence with 405 nm excitation and detection at wavelengths greater than 500 nm were also used to acquire images for comparison. Crossed polarizers were used for reflectance measurements to reduce interference from specular reflectance. Results The contrast of both the 1‐ and 2‐day lesions were significantly higher (P < 0.05) for near‐IR reflectance imaging at 1, 460 and 1, 600 nm than it was for near‐IR reflectance imaging at 1, 300 nm, visible reflectance imaging, and fluorescence. Conclusion The markedly higher contrast at 1, 460 and 1, 600 nm wavelengths, coincident with higher water absorption, suggest that these wavelengths are better suited than 1, 300 nm for imaging early/shallow demineralization on tooth surfaces. Lasers Surg. Med. 45:533–541, 2013. © 2013 Wiley Periodicals, Inc.